Job loss and household labor supply adjustments in developing countries: Evidence from Argentina - Matías Ciaschi; Guido Neidhöfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Using longitudinal data for Argentina, we estimate the labor supply reaction of spouses and children to their husband's or father's job loss. Our findings show that job loss by the household head has a positive and significant impact on the labor supply of other household members. However, it increases the likelihood of spouses to switch to informal and downgraded employment, and of children to drop-out from education. While effects are stronger among vulnerable households, coverage of social security does not provide enough support in coping with unemployment shocks. Instead, we find that mothers' labor participation may prevent the educational drop-out of their daughters.
Keywords: J16; J21; J22; J65; 330; Job loss; Labor supply; Female labor participation; Educational enrollment; Educational drop-out; Human capital formation; Idiosyncratic shocks